Influence of sand grain size distribution and supplementary cementitious materials on the compressive strength of ultrahigh-performance concrete - Bassam A. Tayeh; Mahmoud H. Akeed; Shaker Qaidi; B.H. Abu Bakar (Case Studies in Construction Materials, 2022)
ultrahigh-performance concrete is a type of advanced concrete that can improve the resilience and durability of concrete structures. The utilization of available supplementary cementitious materials is a critical step in saving energy and materials, as well as lowering the cost of concrete. This research investigated the impact of sand grain size distribution, supplementary cementitious materials, and curing regimes (CRs) on the compressive strength of ultrahigh-performance concrete. The findings showed that a 90-d strength of 175 MPa could be obtained with a microsilica volume of 5 % and without heat-curing. The highest strength was obtained after curing for 48 h at 60 °C, followed by 72 h at 90 °C. Moreover, when compared to natural grain size distribution sand, the usage of finer sand enhances compressive strength. When microsilica is added, however, this impact is minimized.